Developing Akhlak Karimah Values through Integrative Learning Model in Madrasah - Syamsul Arifin; Nur Hayati Mufida; Miftachul Huda (Jurnal Pendidikan Islam, 2023)
The primary objective of this study was to examine a holistic learning approach that promotes the development of noble character values (akhlak karimah) in madrasah. The study employed a qualitative methodology, specifically utilizing phenomenological research and a descriptive method. Data collection involved interviews, observations, and examination of relevant documents. The participants in this research were Madrasah teachers responsible for teaching various subjects at the ibdtida'iyah, tsanawiyah, and aliyah levels in Lombok. The findings revealed the development of a learning model that integrates all aspects of education to foster the exploration of akhlak karimah values, which are defined as objectives in the affective domain. These values were identified based on the students' needs and were subsequently incorporated into the curriculum through student-centered integrated learning. The implementation of the proposed model follows a similar pattern and concludes with a dedication to this approach.